Precalculus : algebraic and trigonometric functions, vol. 4 : Polynomial and rational functions. (San Rafael, California : Individual Learning Systems, Inc., 1971)
In units two and four your learned to solve first and second degree polynomial equations and to construct the graphs of first and second degree polynomial functions. In unit five you will learn theorems that apply to all polynomials.
Unit Five: Polynomial and rational functions -- Module 16. Introduction to Polynomials -- Module 17. Rule of signs, division algorithm, remainder theorem, and synthetic division -- Module 18. Additional theorems of polynomials -- Module 19. Rational roots and the depressed equation -- Module 20. Constructing graphs of polynomial functions; rational functions.
Keywords: PRECALCULUS -- POLYNOMIAL -- RATIONAL FUNCTIONS